CENTRAL ANGIOTENSIN-CONVERTING ENZYME-BLOCKADE AND THIRST - Saad, W. A.; Luiz, A. C.; Camargo, LAA; Menani, José Vanderlei [UNESP]; Renzi, Antonio [UNESP]; Silveira, JEN (Associação Brasileira de Divulgação Científica (ABRADIC), 1993)
1. The effect of lisinopril, a potent inhibitor of angiotensin converting enzyme (ACE), injected into the medial preoptic area (MPOA) on water intake was investigated in male Holtzman rats (200-250 g).2. Injection of lisinopril (2 mug/mul) into the MPOA abolished the water intake induced by subcutaneous (sc) injection of isoprenaline (100%) and water deprivation (90%) and drastically reduced the water intake induced by sc injection of polyethyleneglycol (60%). A small reduction of water intake induced by lisinopril was also observed 90 and 120 min after sc hypertonic saline (N = 10 for each group).3. These results suggest that central ACE activation, particularly in the MPOA, plays an important role in the dipsogenic responses induced by the agents studied.
Keywords: WATER INTAKE; DEHYDRATION; HYPOVOLEMIA; ANGIOTENSIN-II; LISINOPRIL; MEDIAL PREOPTIC AREA